Comparison of calcareous replacement hemiarthroplasty and proximal femoral nail in elderly ıntertrochanteric femur fractures - Erkmen, Deniz; Oken, Ozdamar F.; Demirtaş, Yunus (International Journal of Research in Orthopaedics, 2023)
Background: In this study, a retrospective evaluation was made of patients aged 70 years and over who were applied with proximal-femoral nail (PFN) or calcareous replacement cemented hemiarthroplasty in respect of early and late-stage morbidity and mortality and functional personal independence. Methods: The study included a total of 77 patients aged over 70 years with an AO type 31-A1 or 31-A2 fracture. The patients were separated into two groups as those applied with proximal femoral nailing and those applied with calcar replacement hemiarthroplasty. Statistical comparison was made of the groups in respect of preoperative age, comorbidities, type of anaesthesia, ASA score, and fracture type, and postoperative amount of blood loss, albumin decrease, wound complications, other complications, Harris hip functional scores, Barthel daily living activity index, mortality rates. Results: The two groups were found to be similar in respect of age, gender, comorbidities, AO fracture type and type of anaesthesia. The operating time was shorter in the proximal femoral nailing group. The Harris hip scores and the Barthel daily living activity ındex values were similar in both groups. Rates of wound infection were higher in the hemiarthroplasty group. Mortality rates at one month, six months and one year were similar in both groups. Conclusions: Proximal femoral nailing can be one of the primary treatment options for intertrochanteric hip fractures in the elderly. Furthermore, although functional results and mortality rates are similar, as cemented calcar replacement hemiarthroplasty has serious life-threatening complications, it should not be the first choice of treatment method.